2000
DOI: 10.1034/j.1600-0528.2000.028005373.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary alterations in type 2 (non‐insulin‐dependent) diabetes mellitus and hypertension

Abstract: The pattern of decreased flow rates and increased protein concentrations were similar, but consistently greater in diabetics than hypertensives, suggesting that disease-specific mechanisms may be responsible. Diabetics may be more prone to oral dryness and infections than non-diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 35 publications
7
69
1
6
Order By: Relevance
“…[18][19][20] Bilateral enlargement of the parotid salivary glands has been reported to occur in 10-48% of diabetic patients 21,22 and may be more common in patients with poorly controlled diabetes. 23 The enlargements are caused by gradual accumulation of fat in the glands, hypertrophy of the acini or secreting units, and, eventually, impaired glandular secretion.…”
Section: Salivary Gland Changesmentioning
confidence: 99%
“…[18][19][20] Bilateral enlargement of the parotid salivary glands has been reported to occur in 10-48% of diabetic patients 21,22 and may be more common in patients with poorly controlled diabetes. 23 The enlargements are caused by gradual accumulation of fat in the glands, hypertrophy of the acini or secreting units, and, eventually, impaired glandular secretion.…”
Section: Salivary Gland Changesmentioning
confidence: 99%
“…Similar results were obtained in type 1 diabetic children; diabetics had neither salivary total protein nor albumin concentrations that were significantly different from controls, however, IgA and IgG levels were increased (12). In a large study performed in non-insulin-dependent diabetic patients, a significant increase of the concentration of lactoferrin, myeloperoxidase, and salivary peroxidase in stimulated parotid saliva, and of total protein, albumin, lactoferrin, and secretory IgA in stimulated submandibular/sublingual saliva was shown with respect to controls (13). In the same study it was also established that submandibular/sublingual salivary cystatin concentration did not significantly differ between diabetics and controls.…”
mentioning
confidence: 99%
“…Lactoferrin detection has been related to periodontitis (Komine et al, 2007), type 2 diabetes mellitus (Dodds et al, 2000), and Sjö gren's syndrome both by ELISA and Western blotting (Carpenter et al, 2000). Although only a few biomarkers are confirmed by other methods, several biomarkers found in most studies were not confirmed by other analyses or by other non-MS methods.…”
mentioning
confidence: 99%